PENGARUH PEMBELAJARAN SAVI BERBASIS MEDIA SIMULASI INTERAKTIF TERHADAP KETERAMPILAN BERPIKIR KRITIS MAHASISWA PADA MATERI ELEKTROKIMIA - Dewi, Citra Ayu; Ahmadi, Ahmadi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
Characteristics of electrochemical material that contains abstract concepts. Hence often have difficulty in teaching it. An effective approach as a solution is the SAVI-based interactive learning approach of interactive simulation. Learning SAVI-based interactive media has an animation program that is able to represent abstract concepts in electrochemical materials through visualization and not illustration of the concept in narrative. The purpose of this research is to know the influence of SAVI learning approach to students' critical thinking skill in electrochemical material. The type of research used is quasi-experimental research. The research design used is posttest only control group design. The sample was divided into two groups: experiment and control group. The research instrument uses critical thinking skill test through rubric. The results show that the SAVI approach has a positive effect on critical thinking skills compared to conventional methods. We conclude that the SAVI learning approach has been able to improve students' critical thinking skills.